PEMBARUAN PEMASARAN TERHADAP VOLUME PENJUALAN PRODUK AYAM PEDAGANG DI KOTA BEKASI - Paduloh Paduloh; Andika Maulana, Farrel Ihsan Aditya, Dwi Hardiyana Saputra, Teguh Prasetyo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The aim of this research is to analyze the impact of the marketing mix. The design of this research is a cross-sectional study with a sample size of four groups, which were taken randomly using the exchange sampling method. Data collection was carried out through observation, interviews and questionnaires. Chi-square test and linear regression were used to analyze the data. Linear regression to find the most influential independent variable. This study found that there were three influential variables: product marketing mix (p = 0.032), price (p = 0.001), and product distribution (p = 0.020), with price having the largest impact on sales. Sig (p) = 0.010 (beta = 0.282). Traders are expected to further improve the marketing mix of broiler chicken products in terms of aspects (product, price and distribution) so that chicken sales can be increased. Traders need to make more careful considerations, such as determining selling prices, prices imposed by competitors and costs incurred in connection with efforts to increase sales